2014
DOI: 10.1155/2014/697491
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Corrosion Studies of Surface Modified NiTi Alloy for Biomedical Applications

Abstract: Electropolishing was conducted on NiTi alloy of composition 49.1 Ti-50.9 Ni at.% under potentiostatic regime at ambient temperature using perchloric acid based electrolyte for 30 sec followed by passivation treatment in an inorganic electrolyte. The corrosion resistance and biocompatibility of the electropolished and passivated alloys were evaluated and compared with mechanically polished alloy. Various characterization techniques like scanning electron microscopy, atomic force microscopy, and X-ray photoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…Furthermore, the corrosion rate (ʋ corr ) of the bare NiTi alloy was 1.606 × 10 −5 mm/yr, whereas that of the GO-coated NiTi was 1.129 × 10 −6 mm/yr and for GO/Ag-coated NiTi was 1.961 × 10 −7 mm/yr. The corrosion rate of the bare NiTi in our study lies in between the results of other studies done by Zhang et al 37 (2.4 × 10 −4 mm/yr) and Chembath et al 30 (6.98 × 10 −6 mm/yr). Furthermore, Zhang et al 37 found that the corrosion rate of GO-coated NiTi alloy to be 1.4 × 10 −5 mm/yr but in our studies the GO-coated NiTi showed better corrosion resistance (1.129 × 10 −6 mm/yr) than theirs.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the corrosion rate (ʋ corr ) of the bare NiTi alloy was 1.606 × 10 −5 mm/yr, whereas that of the GO-coated NiTi was 1.129 × 10 −6 mm/yr and for GO/Ag-coated NiTi was 1.961 × 10 −7 mm/yr. The corrosion rate of the bare NiTi in our study lies in between the results of other studies done by Zhang et al 37 (2.4 × 10 −4 mm/yr) and Chembath et al 30 (6.98 × 10 −6 mm/yr). Furthermore, Zhang et al 37 found that the corrosion rate of GO-coated NiTi alloy to be 1.4 × 10 −5 mm/yr but in our studies the GO-coated NiTi showed better corrosion resistance (1.129 × 10 −6 mm/yr) than theirs.…”
supporting
confidence: 89%
“…The surface roughness (R a ) determined from the AFM is 7.55 ± 1.7 for the bare NiTi, 11.67 ± 2.03 for the GO-coated NiTi, and 18.43 ± 2.43 nm for the GO/Ag-coatings NiTi alloys. Chembat et al 30 found the R a of the bare NiTi alloy around 1.7 ± 0.1 nm. Similarly, Abdul et al 31 studied on the graphene composite coatings on carbon steel and found the surface roughness (Ra) were 34 to 150 nm according to deposition temperature where they measured using AFM.…”
mentioning
confidence: 97%
“…From Table 2, the CPE measured on the PG coated nickeltitanium surfaces behaved like ideal capacitors (n ≈ 1), while in Table 3, this behaviour in the TA coated group between 12 and 24 h, changed to a Warburg diffusion component (n ≈ 0.5). The drop of the Q f and n values in the TA group suggests the development of a more porous coating layer, in agreement with Chembath et al [31]. This is reflected in the CPE values which follow the order TA<PG after 24 h immersion in the PBS+BSA solution.…”
Section: Constant Phase Element Cpesupporting
confidence: 90%
“…Different surface modification techniques such as heat treatment, chemical etching, laser and electron beam irradiation, ion implantation and electrochemical treatment have been employed to decrease the release of Ni and to enhance the biocompatibility of the Ni–Ti alloy. These methods have been focused at forming uniform oxide layer on Ni–Ti surfaces.…”
Section: Introductionmentioning
confidence: 99%